The Medial Tibial Plateau Can Be Used as a Direct Anatomical Reference for the Posterior Tibial Slope in Medial Unicompartmental Knee Arthroplasty - Mori, Shigeshi; Akagi, Masao; Moritake, Akihiro; Tsukamoto, Ichiro; Yamagishi, Kotaro; Inoue, Shinji; Nakagawa, Koichi; Togawa, Daisuke (The Journal of Knee Surgery, 2021)
There has been no consensus about how to determine the individual posterior tibial slope (PTS) intraoperatively. The purpose of this study was to investigate whether the tibial plateau could be used as a reference for reproducing individual PTS during medial unicompartmental knee arthroplasty (UKA). Preoperative computed tomography (CT) data from 48 lower limbs for medial UKA were imported into a three-dimensional planning software. Digitally reconstructed radiographs were created from the CT data as the lateral knee plain radiographs and the radiographic PTS angle was measured. Then, the PTS angles on the medial one-quarter and the center of the MTP (¼ and ½ MTP, respectively), and that on the medial tibial eminence (TE) were measured on the sagittal multiplanar reconstruction image. Finally, 20 lateral knee radiographs with an arthroscopic probe placed on the ¼ and the ½ MTP were obtained intraoperatively, and the angle between the axis of the probe and the tangent line of the plateau was measured. The mean radiographic PTS angle was 7.9 ± 3.0 degrees (range: 1.7–13.6 degrees). The mean PTS angles on the ¼ MTP, the ½ MTP, and the TE were 8.1 ± 3.0 degrees (1.2–13.4 degrees), 9.1 ± 3.0 degrees (1.4–14.7 degrees), and 9.9 ± 3.1 degrees (3.1–15.7 degrees), respectively. The PTS angles on the ¼ MTP and the ½ MTP were strongly correlated with the radiographic PTS angle (r =0.87 and 0.80, respectively, p < 0.001). A statistically significant difference was observed between the mean angle of the radiographic PTS and the PTS on the TE (p < 0.01). The mean angle between the axis of the probe and the tangent line of the tibial plateau was −0.4 ± 0.9 degrees (−2.3–1.3 degrees) on the ¼ MTP and −0.1 ± 0.7 degrees (−1.5–1.2 degrees) on the ½ MTP, respectively. An area from the medial one-quarter to the center of the MTP could be used as an anatomical reference for the individual PTS.
Keywords: anatomical reference; posterior tibial slope; tibial plateau; unicompartmental knee arthroplasty; digital reconstruction radiograph